MORAL VALUES ANALYSIS AS SEEN ON NINE FILM - Asmila Asmila; Dodi Oktariza; Rini Afrilesa J (Universitas Muara Bungo, 2022)
This study analyzes the moral values contained in the film Nine 2009. The purpose of this study is to describe the types of moral values and describe the impact of moral values contained in the film Nine in 2009.In this study, the writer uses a qualitative descriptive method proposed by Creswell (1994:45) which uses descriptive techniques to describe and analyze the data. The data were analyzed in several ways, namely identification, classification, analysis and conclusion. In this study, the writer uses the theory of moral values from Guerin (2005) and the theory of Webster (1981) as the basis for the types of moral values of the researcher's theory.From the results of the study obtained types of moral values such as courage, enthusiasm, kind, honesty, love and compassion, loyalty, love of peace, perseverance, sacrifice for others, self-confidence, and based on strong beliefs. on Webster's (1981) theory. In Nine, the writer finds six (7) courage, two (2) loyalty, two (2) love and compassion, three (3) sacrifices for others and two self-confidence. The writer also explains the impact of moral values on the film Nine. The writer finds two kinds of impacts, namely the good impact and the bad impact on the film Nine. One of the good effects is cohesiveness in friendship and the bad effect is selfishness that causes death. From the data obtained, the key that the most dominant type of moral value found in the 2009 film Nine is Courage. And the writer finds two kinds of good impacts and bad impacts.